The Effect of Show and Tell Method on Students’ Speaking Skill of the Tenth AKL (Akuntansi dan Keuangan Lembaga) Grade at SMK Sritanjung Banyuwangi - Reggina Rismayani; Wulan Wangi; Nur Hasibin (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2025)
A valuable learning environment is influential to improve speaking skills among students. Teachers need to apply more learning approach to engage the students effectively and lead to optimalized their speaking skill improvement. There is a method that is accepted to enhance students' speaking skill, and it is called as Show-and-Tell method. The objective of this research is to determine wether there is any effect or not about show and tell method on students’ speaking skills of the tenth AKL grade at SMK Sritanjung Banyuwangi. This research used pre-experimental quantitative (one-group pre-test and post-test design). The researchers used monologue oral test in collecting the data. There were nine students of the tenth AKL grade in this research. The data was calculated by using SPSS Calculation of Wilcoxon Test. The results showed that there was effect of Show and Tell Method on students’ speaking skills of the tenth AKL grade at SMK Sritanjung Banyuwangi. Since this method is interactive, it is well-suited to address the speaking challenges faced by students at SMK Sritanjung Banyuwangi.